Glycolipids as Immune Modulatory Tools - Lalazar, Gadi; Preston, Sarah; Zigmond, Ehud; Ben Yaacov, Ami; Ilan, Yaron (Mini Reviews in Medicinal Chemistry, 2006)
NKT cells are a subset of regulatory lymphocytes characterized by co-expression of the NK cell receptor- CD161 and an invariant TCR-α chain (Vα14-Jα28). They are most abundant in the liver, spleen, and bone marrow. NKT lymphocytes have been implicated in the regulation of autoimmune processes in both mice and humans. Activation of NKT lymphocytes leads to rapid amplification of either IFNγ or IL4, endowing these cells with the capability to mediate both pro-inflammatory and anti-inflammatory immune responses. Activation of this subset of cells is associated with significant liver damage in the Concanavalin A immune mediated hepatitis model. Administration of CD1d ligand has a protective role in collagen-induced arthritis in mice. Disease amelioration was associated with a shift in the immune balance from a pathological Th1 type response towards a protective Th2 type response. In humans, patients with SLE, scleroderma, diabetes, multiple sclerosis, and rheumatoid arthritis have lower numbers of peripheral NKT cells. NKT lymphocytes promote tumor rejection in experimental models of tumor immunotherapy. In contrast, NKT lymphocyterelated anti-tumor activity is associated with pro-inflammatory Th1-type immune responses. NKT cells were shown to have a role in suppression of hepatocellular carcinoma (HCC) via immune regulation towards tumor derived antigens, and adoptive transfer of dendritic cells pulsed ex vivo with the same antigens. NKT lymphocytes are activated by interaction of their TCR with glycolipids presented by CD1d, a nonpolymorphic, MHC class I-like molecule expressed by antigen presenting cells, and also by hepatocytes. Several possible ligands for NKT cells have recently been suggested including CD1d bound Glucocerebroside. Glucocerebroside (GC, β- glucosylceramide), a naturally occurring glycolipid, is a metabolic intermediate in the anabolic and catabolic pathways of complex glycosphingolipids. Its synthesis from ceramide is catalyzed by the enzyme glucosylceramide synthase. Inherited deficiency of glucocerebrosidase, a lysosomal hydrolase, results in Gaucher's disease. Patients with Gaucher's disease have altered humoral and cellular immune profiles and increased peripheral blood NKT lymphocytes. CD1d-bound glucocerebroside does not activate NKT cells directly, and may inhibit activation of NKT cells by α-GalCer. On the other hand, glucosylceramide-synthase deficiency was shown to lead to defective ligand presentation by CD1d, with secondary inhibition of NKT cell activation. Recent studies have suggested that a number of glycolipids, including GC, have an immune modulatory effect in several immune mediated disorders. The ability to alter NKT lymphocyte function in various settings and the potential application of natural glycolipids for treatment are discussed.
Keywords: CD1 proteins